Emotions among the primary schools: a Malay drama program (Software) / Dr Normaliza Abd Rahim and Nik Ismail Harun - Abd Rahim, Normaliza; Harun, Nik Ismail (2011)
Emotions are very complex experiences and, to express them, we use a great variety of terms, besides gestures and attitudes. Emotions involve a wide variety of feelings, thoughts, and behavior. The experiences that cause emotions are subjective experiences, or experiences from an individual point of view. Emotions for children are often associated with mood, temperament, personality, and disposition. Therefore, this study concentrates on 100 subjects from two primary schools in Malaysia. The objectives of the study were to find out the types of emotions while carrying out the tasks and to discuss the content of discussion of the subjects after the program. The subjects were picked at random and a program or software which consists of Malay short dramas and questions was given to the subjects. The subjects were in pairs or individual. The subjects' discussions and conversations were taped for forty-five minutes. The conversations were analyzed and the subjects' emotions were identified.